2021
DOI: 10.1186/s13765-021-00657-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of genetic and environmental factors on the contents of carotenoids and phenolic acids in red pepper fruits (Capsicum annuum L.)

Abstract: Red pepper is enriched in antioxidant components, such as carotenoids, phenolic compounds, and vitamins. In this study, we investigated the natural variability in the content of carotenoids and phenolic acids in 11 red pepper cultivars grown in two locations in South Korea during 2016, 2017, and 2018. Seven carotenoids and six phenolic acids, including soluble and insoluble forms, were detected in the red fruit pericarps. The major carotenoids were β-carotene (40%) and capsanthin (20%). The content of insolubl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Though crop metabolite profiling is an important area of nutritional and health research, this information can also be used for the classification of peppers. Principal components and partial least discriminant analyses are relevant for the classification of metabolomic datasets based on different factors such as variety, location, and their interactions [ 32 ]. In the current study, the jalapeño and serrano type chile peppers were differentiated based on their metabolite profiles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though crop metabolite profiling is an important area of nutritional and health research, this information can also be used for the classification of peppers. Principal components and partial least discriminant analyses are relevant for the classification of metabolomic datasets based on different factors such as variety, location, and their interactions [ 32 ]. In the current study, the jalapeño and serrano type chile peppers were differentiated based on their metabolite profiles.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolomics can render insights into the different metabolites which can be targeted further for breeding and selection using different genomics tools such as metabolite-quantitative trait loci (mQTL) analyses, metabolite-based genome-wide association studies (mGWAS), and metabolite-genome predictions [ 50 ]. Variation in the phenolic acid content in chile peppers is affected by the varietal type, location, and growing season, and, hence, can impose challenges on performing breeding and selection [ 32 ]. Given the complex nature of these phenotypes, caution must be observed when performing the collection of fruit samples for metabolomics analyses to minimize the errors and variation due to sampling.…”
Section: Discussionmentioning
confidence: 99%
“…The most abundant phenolic compound found in the extracts was vanillic acid (7.97-12.66 µg/mg), but no signi cant effects of time or temperature of extraction were observed (Table 1). Kim et al after analyzed the methanolic extracts of 11 chili pepper varieties found out that the main phenolic compounds in the extracts from the fruits were p-hydroxybenzoic, vanillic, p-coumaric, ferulic and sinapic acids [14]. Similarly, Dos Anjos et al found that on Brazilian chili pepper (Capsicum frutescens) pericarp one of the main phenolic compounds was vanillic acid (1.9 µg/mg) [15].…”
Section: Phenolic Compounds Pro Le and Quanti Cationmentioning
confidence: 99%
“…For the chili peppers, carotenoids contribute to the coloration of the mature states, which is evident as the chlorophyll degrades ( 48 , 49 ). In this regard, it is worth highlighting the marked influence of environmental conditions and the genetics of chili peppers regarding the accumulation of carotenoids, which have been regularly identified in various chili genotypes, where specific accumulation patterns have been observed ( 50 52 ). As an example, in the piquin chili, the carotenoid content has been reported as contrasting between the immature (green fruit) and mature states (red fruit), in addition to being undetectable in the first state and reaching considerable levels when ripe ( 33 ).…”
Section: Carotenoidsmentioning
confidence: 99%
“…Two ecotypes of piquin chili from Tabasco State (southeastern Mexico) showed significant differences between carotenoid contents in ripe and unripe fruits. Mature fruits show higher carotenoid content and are subjected to various levels of shading, reaching up to 28.80 mg g −1 of DW in the dry season, in an open sky system for the Garbanzo genotype and 23.71 mg g −1 of DW in the rainy season, in an open sky system for the Amashito genotype ( 50 ). The same research shows a difference in carotenoid levels in mature chili peppers, and these differ according to the shading conditions, with higher levels when the plants are exposed to natural light in the open field system and lower levels when shade conditions are increased.…”
Section: Carotenoidsmentioning
confidence: 99%